2019
DOI: 10.1186/s40425-019-0691-0
|View full text |Cite
|
Sign up to set email alerts
|

miR-448 targets IDO1 and regulates CD8+ T cell response in human colon cancer

Abstract: Background Indoleamine 2,3-dioxygenase 1 (IDO1) is a critical regulator of T cell function, contributing to immune tolerance. Upregulation of IDO1 has been found in many cancer types; however, the regulatory mechanisms and clinical significance of IDO1 in colon cancer are still unclear. Here, we investigated the role of dysregulated microRNA (miRNA) targeting IDO1 in the colon cancer microenvironment. Methods We elucidated IDO1 function by performing cell-based assays a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(75 citation statements)
references
References 46 publications
1
74
0
Order By: Relevance
“…Besides, Lou et al found that miR-448 acted as a tumor suppressive factor by targeting downstream IDO1 in colon cancer cells. The results of in vitro study showed that the ectopic expression of miR-448 was beneficial to giving full play to the functions of TILs [124]. Moreover, Huang et al reported that miR-153 level was a core factor determining the efficacy of chimeric antigen receptor (CAR) T cells treatment in colon cancer models.…”
Section: Cancer Cell Metabolite-related Mirnasmentioning
confidence: 99%
“…Besides, Lou et al found that miR-448 acted as a tumor suppressive factor by targeting downstream IDO1 in colon cancer cells. The results of in vitro study showed that the ectopic expression of miR-448 was beneficial to giving full play to the functions of TILs [124]. Moreover, Huang et al reported that miR-153 level was a core factor determining the efficacy of chimeric antigen receptor (CAR) T cells treatment in colon cancer models.…”
Section: Cancer Cell Metabolite-related Mirnasmentioning
confidence: 99%
“…Their deregulation in the TME following the development of the disease must be elucidated for their direct impact not only on the proliferation of malignant cells but also on immune TME cells. Interestingly, it was reported that in human colon cancer, miR-448 could suppress CD8+ T-cell apoptosis and enhance the CD8+ T-cell response by inhibiting indoleamine 2,3-dioxygenase 1 enzyme function [ 28 ]. In our results, we also observed other differentially expressed miRNAs, including miR-520a, 651, 520f and 449, that were upregulated in patients and undetectable or expressed at very low levels in HD.…”
Section: Discussionmentioning
confidence: 99%
“…To this end, elevated expression of indoleamine 2,3-dioxygenase 1 (IDO1), an enzyme which metabolizes tryptophan into kynurenine, in the TME has been shown todrive the differentiation of several immunosuppressive cell types [19], including Treg cells [20][21][22], immunosuppressive dendritic cells [23,24] and macrophages [25,26], or to directly suppress anti-tumor immunity [27]. In colorectal cancer, overexpression of IDO1 suppressed the CD8 T cell responses, leading to enhanced tumor growth [27]. In this study, miR-448 was shown to be able to enhance the survival of CD8 T cells by directly attenuating the upregulation of IDO1 in colorectal tumor cells in response to IFNγ stimulation.…”
Section: Immunometabolites Regulated By Mirnasmentioning
confidence: 99%
“…In this study, miR-448 was shown to be able to enhance the survival of CD8 T cells by directly attenuating the upregulation of IDO1 in colorectal tumor cells in response to IFNγ stimulation. Similarly, miR-153 has also been shown to target IDO1 in colorectal cancer in response to IFNγ [27,28]. Moreover, when combining miR-153-mediated IDO1 inhibition and chimeric antigen receptor (CAR) T cell therapy, further enhanced in vitro T cell killing activities and reduced xenograft tumor growth in mice were reported [27,28].…”
Section: Immunometabolites Regulated By Mirnasmentioning
confidence: 99%